Agricultural and Food Systems Sustainability The Complex Challenge of Losses and Waste - Suardi, Alessandro; Palmieri, Nadia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focused on researching food loss and waste in various agricultural supply chains, searching for reduction strategies and possible technological solutions without neglecting the relevance of the socioeconomic factors that influence the functioning of food value chains. The adoption of the 2030 Agenda for Sustainable Development (Goal 12-"Ensure sustainable consumption and production patterns") calls for renewed efforts to reduce food losses along production and supply chains. Achieving this goal will require greater efforts globally to implement food loss reduction policies and interventions. In addition, the sustainable management and use of byproducts from agriculture, including agricultural residues, has been analyzed. Special attention is given to pre- and post-harvesting losses of agricultural products, including the assessment of their environmental and economic sustainability.